Fatigue in multiple sclerosis: The contribution of occult white matter damage. (November 2016) - Bisecco, Alvino; Caiazzo, Giuseppina; d'Ambrosio, Alessandro; Sacco, Rosaria; Bonavita, Simona; Docimo, Renato; Cirillo, Mario; Pagani, Elisabetta; Filippi, Massimo; Esposito, Fabrizio; Tedeschi, Gioacchino; Gallo, Antonio
Background: A functional cortico-subcortical disconnection has been recognized in fatigued multiple sclerosis (MS) patients. Normal appearing white matter (NAWM) damage might contribute to the abovementioned disconnectivity. Objectives: To assess the relationship between fatigue and microstructural NAWM damage in relapsing-remitting (RR) MS. Methods: Sixty RRMS patients and 29 healthy controls (HC) underwent a magnetic resonance imaging (MRI) protocol including diffusion tensor imaging (DTI). Patients with a mean Fatigue Severity Scale (FSS) score ⩾ 4 were considered fatigued (fatigued MS (F-MS)). Tract-based spatial statistics were applied for voxel-wise analysis of DTI indices. A correlation analysis was performed between FSS score and DTI indices in the entire MS group. Results: Thirty MS patients were F-MS. Compared to HC, F-MS patients showed a more extensive NAWM damage than not fatigued MS (NF-MS) patients, with additional damage in the following tracts: frontal and occipital juxtacortical fibers, external capsule, uncinate fasciculus, forceps minor, superior longitudinal fasciculus, cingulum, and pons. No differences were found between F-MS and NF-MS patients. Fatigue severity correlated to DTI abnormalities of corona radiata, cingulum, corpus callosum, forceps minor, superior longitudinal fasciculus, inferior fronto-occipital fasciculus, thalamus and anterior thalamic radiation, cerebral peduncle, and midbrain. Conclusions: Fatigue is associated to a widespread microstructural NAWM damage, particularly in associative tracts connected to frontal lobes.